2013
DOI: 10.1093/hmg/ddt393
|View full text |Cite
|
Sign up to set email alerts
|

Elevated FGF21 secretion, PGC-1α and ketogenic enzyme expression are hallmarks of iron–sulfur cluster depletion in human skeletal muscle

Abstract: Iron-sulfur (Fe-S) clusters are ancient enzyme cofactors found in virtually all life forms. We evaluated the physiological effects of chronic Fe-S cluster deficiency in human skeletal muscle, a tissue that relies heavily on Fe-S cluster-mediated aerobic energy metabolism. Despite greatly decreased oxidative capacity, muscle tissue from patients deficient in the Fe-S cluster scaffold protein ISCU showed a predominance of type I oxidative muscle fibers and higher capillary density, enhanced expression of transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 68 publications
7
43
2
Order By: Relevance
“…Studies have shown that skeletal muscle is an FGF21-producing tissue in mice ( 41 ) and humans ( 42 ) and that mitochondrial respiratory chain defi ciency leads to an induction of FGF21 mRNA expression in skeletal muscle ( 43 ). There is strong evidence that increased FGF21 expression in skeletal muscle of the mutant mouse models and in humans ( 44 ) is causative for increased circulating FGF21 levels. These of murine FGF21.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that skeletal muscle is an FGF21-producing tissue in mice ( 41 ) and humans ( 42 ) and that mitochondrial respiratory chain defi ciency leads to an induction of FGF21 mRNA expression in skeletal muscle ( 43 ). There is strong evidence that increased FGF21 expression in skeletal muscle of the mutant mouse models and in humans ( 44 ) is causative for increased circulating FGF21 levels. These of murine FGF21.…”
Section: Discussionmentioning
confidence: 99%
“…A recent biochemical characterization of ISCU G50E highlighted that the mutation interferes with the ability of the scaffold protein to interact with the sulfur donor NFS1 and with the cochaperone HSC20, thus drastically impairing the rate of Fe-S cluster synthesis [232]. Lack of ISCU in muscle tissue from ISCU myopathy patients elicits activation of a systemic metabolic response leading to increased plasma levels of the starvation response hormone FGF21 (fibroblast growth factor 21) [233]. Interestingly, the incorrect splicing of the ISCU mRNA is more pronounced in muscle than in other tissues, resulting in a muscle-specific phenotype.…”
Section: Iscu Myopathy Also Known As Hereditary Myopathy With Lacticmentioning
confidence: 99%
“…Interestingly, the incorrect splicing of the ISCU mRNA is more pronounced in muscle than in other tissues, resulting in a muscle-specific phenotype. Moreover, the differentiation level of muscle fibers was shown to enhance aberrant splicing of ISCU, as the muscle- specific transcription factor MyoD1 decreased the amount of normal ISCU transcript in patient myoblasts [233]. Several studies were carried out to understand the molecular mechanisms that may contribute to the tissue specific phenotype of the disease, and five nuclear factors were found to interact with the sequence harboring the mutation [234], including three splicing factors, SFRS14, RBM39, and PTBP1, and two additional RNA binding factors, matrin 3 (MATR3) and IGF2BP1.…”
Section: Iscu Myopathy Also Known As Hereditary Myopathy With Lacticmentioning
confidence: 99%
“…In contrast, mitoferrin-2 did not support mitochondrial iron supply in erythroblasts. In mouse models of Friedreichs ataxia Martelli et al, 2015) and in patients suffering from a muscle-specific ISCU deficiency (Crooks et al, 2014), MFRN2 expression levels are increased, eventually resulting in facilitated mitochondrial iron influx. Hence, under pathological conditions, MFRN2 likely contributes to excess mitochondrial iron loading, a hallmark of human diseases related to impaired mitochondrial ISC assembly (Delatycki et al, 1999;Martelli and Puccio, 2014;Puccio et al, 2001).…”
Section: The Mitochondrial Inner Membrane Transportersmentioning
confidence: 99%